Queer Disidentification: Or How to Cook Chinese Noodles in a Global Pandemic? - Hongwei Bao (PORTAL: Journal of Multidisciplinary International Studies, 2021)
In this article, I offer a critical analysis of a video artwork titled Lerne Deutsch in meiner Küche (Learn German in My Kitchen) (2020), created by Berlin-based queer filmmaker Popo Fan. By focusing on Fan’s negotiation of racial, ethnic, and cultural identities in the video, I argue that Fan’s artwork offers a way to reimagine identities away from the identity politics that are widely circulated in the current pandemic discourse. My analysis draws on José Esteban Muñoz’s (1999) notion of ‘disidentification,’ which describes minority subjects’ complex processes of identification—in particular, instances of identifying partially, conditionally and contingently—with dominant identities, discourses and ideologies. In doing so, I unravel the intricate politics of identity in the current global pandemic and highlight the role of queer disidentification as an important critical intervention in the current political debate about the COVID-19 pandemic.